Rojam health products: Innovation for growth and organizational sustainability - Hasan, Quamrul; Abdul Rahim, Mohd Kamarul Irwan; Taib, Che Azlan (2017)
Penawar Industries Sdn Bhd (Penawar), founded by Haji Shuib Mohd Isa (Hj Shuib) in Kedah as an SME, had been manufacturing the healthcare and cosmetic products under the brand name of ROJAM since 1992. During the past several years, Penawar had been struggling in sustaining the market share.The annual sales have started to drop significantly since 2001.On top of that, in 2008, the marketing manager who was very productive left the company due to family reason.Hj Shuib failed to find a new marketing manager who could replace the previous one with enough skills and high productivity.This added further headache to Hj Shuib.The company’s sales dropped to more than 80% in 2010 as compared with the peak year in 1998.The business result was getting bad and bad in a year by year which became worse in 2015. Hj Shuib finally took some crucial actions for sustainability of the company he founded.One of such key actions was to assign Hajah Rodina Shuib, the finance director and one of his daughters, for taking the responsibility of the factory effective from June 2015.